2017
DOI: 10.14295/oh.v23i4.1098
|View full text |Cite
|
Sign up to set email alerts
|

Production of calla lily grown in an NFT system

Abstract: The objective of this study was to evaluate the production of calla lily in an NFT system. The experiment was carried out in a greenhouse, using a 2 x 2 factorial scheme in a completely randomized design (CRD), with fifteen replications. The treatments were a combination of two hydroponic profiles (100 and 150 mm of height) and two nutrient solutions. Calla lily plantlets obtained from rhizome buds in trays containing nutrient solution, Palavras-chave:Zantedeschia aethiopica, floricultura, hidroponia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Landgraf et al (2015) also found that the initial development of calla lily was not affected by the solution in their NFT system (Landgraf et al, 2015), indicating that in this initial phase, the formulations used were equally efficient. However, in the production phase, the specific formulation is relevant (Landgraf et al, 2017). The different systems tested here, semihydroponic and ebb-and-flow, were efficient for the initial development of the calla lily.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Landgraf et al (2015) also found that the initial development of calla lily was not affected by the solution in their NFT system (Landgraf et al, 2015), indicating that in this initial phase, the formulations used were equally efficient. However, in the production phase, the specific formulation is relevant (Landgraf et al, 2017). The different systems tested here, semihydroponic and ebb-and-flow, were efficient for the initial development of the calla lily.…”
Section: Discussionmentioning
confidence: 98%
“…The authors used similar solutions as there were tested in this studyboth "Fruit" and "Leaf" solutions (Landgraf et al, 2015). In order study, Landgraf et al, 2017 identified that the "Fruit Solution" provided better results for calla lily production. Due to that e in order to improve and aiming for a better result, the compositions of the nutrient solutions used in that study were adapted from those previously tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations